Purine metabolism controls innate lymphoid cell function and protects against intestinal injury. Issue 10 (10th July 2018) - Crittenden, Siobhan; Cheyne, Ashleigh; Adams, Alexander; Forster, Thorsten; Robb, Calum T; Felton, Jennifer; Ho, Gwo‐Tzer; Ruckerl, Dominik; Rossi, Adriano G; Anderton, Stephen M; Ghazal, Peter; Satsangi, Jack; et al.
Abstract: Inflammatory bowel disease (IBD) is a condition of chronic inflammatory intestinal disorder with increasing prevalence but limited effective therapies. The purine metabolic pathway is involved in various inflammatory processes including IBD. However, the mechanisms through which purine metabolism modulates IBD remain to be established. Here, we found that mucosal expression of genes involved in the purine metabolic pathway is altered in patients with active ulcerative colitis (UC), which is associated with elevated gene expression signatures of the group 3 innate lymphoid cell (ILC3)–interleukin (IL)‐22 pathway. In mice, blockade of ectonucleotidases (NTPDases), critical enzymes for purine metabolism by hydrolysis of extracellular adenosine 5′‐triphosphate (eATP) into adenosine, exacerbates dextran‐sulfate sodium‐induced intestinal injury. This exacerbation of colitis is associated with reduction of colonic IL‐22‐producing ILC3s, which afford essential protection against intestinal inflammation, and is rescued by exogenous IL‐22. Mechanistically, activation of ILC3s for IL‐22 production is reciprocally mediated by eATP and adenosine. These findings reveal that the NTPDase‐mediated balance between eATP and adenosine regulates ILC3 cell function to provide protection against intestinal injury and suggest potential therapeutic strategies for treating IBD by targeting the purine–ILC3 axis. Abstract : The purine metabolic pathway has been indicated to be involved in Inflammatory bowel disease, but the mechanisms remain to be established. We have found in this research that metabolic regulation of eATP into adenosine by NTPDases promotes ILC3–IL‐22 protection against acute intestinal epithelial injury. These findings suggest that targeting the purine‐ILC3 axis could represent new therapeutic strategies against intestinal injury and inflammation.